2019
DOI: 10.1108/inmr-02-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of student entrepreneurship

Abstract: Purpose -The purpose of this paper is to analyze this phenomenon and identify its determinants using data from Brazilian higher education institutions.Design/methodology/approach -Based on a data set comprehending 2,230 university students from 70 different institutions across the country, the authors develop five Probit models to assess impacts related to individual traits and systemic conditions on five dependent dimensions: entrepreneurial activity, potential entrepreneurs, high-impact entrepreneurship, ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 76 publications
0
46
0
12
Order By: Relevance
“…First, this study did not consider individual attributes because of a lack of relevant data. Personal attributes such as age, gender, discipline, and family income play a fundamental role in the recognition of start-ups and numerous studies have explained the determinants of individual attributes in start-ups [6][7][8]. However, in this study, individual determinants were not considered and these limitations may lead to bias in the research results.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…First, this study did not consider individual attributes because of a lack of relevant data. Personal attributes such as age, gender, discipline, and family income play a fundamental role in the recognition of start-ups and numerous studies have explained the determinants of individual attributes in start-ups [6][7][8]. However, in this study, individual determinants were not considered and these limitations may lead to bias in the research results.…”
Section: Discussionmentioning
confidence: 92%
“…As a resource influencing student start-ups, university funding for start-ups was positive and significant, whereas government funding was not significant. It has previously been shown that providing start-up funding has a positive and significant effect on start-ups [6], most likely because such funding enables the creation of business plans, facilitates market research, and allows for the production of prototypes [63]. In addition, financial support from universities can play a critical role in the early stages of start-ups, as it can be difficult to secure external venture capital or attract an angel investor [64].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations